2023
DOI: 10.1088/1755-1315/1183/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Drip irrigation system: useful technique to improve chili production

I Cartika,
R Murtiningsih,
A Sembiring
et al.

Abstract: The effects of climate change such as continuing reduces of the water availability and quality contributed to the declining the agricultural production. The production of chili, one of the vegetable commodities that high economic value in Indonesia, are also affected by this limited water availability. The current research to develop technology on the drip irrigation utilization aims to increase chili production using efficient water technology. The experiment was carried out at the Margahayu Research Station,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The study of a similar issue was carried out by I. Cartika et al (2023). Their results revealed that the drip irrigation method can increase yields by 8.39%, reduce costs of chilli pepper production by 13.04% and increase farmers' income by 9.25% compared to manual irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…The study of a similar issue was carried out by I. Cartika et al (2023). Their results revealed that the drip irrigation method can increase yields by 8.39%, reduce costs of chilli pepper production by 13.04% and increase farmers' income by 9.25% compared to manual irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Drought-stressed plants can release volatile substances that draw pests and make pest assaults more likely [17]. Regarding watering schedules, insufficient hydration may be the cause of the significant output losses at 25% and 50% ETc, which would affect plant growth and metabolic processes [25]. The prolonged leaf wetness caused by constant exposure to rain and dew encourages the growth and dissemination of bacterial and fungal infections [26].…”
Section: Pestmentioning
confidence: 99%